PENGARUH TINGKAT PENDIDIKAN, LATAR BELAKANG PENDIDIKAN, PENGALAMAN DAN FAKTOR SOSIAL TERHADAP PEMANFAATAN CATATAN ATAS LAPORAN KEUANGAN (CALK) PADA SKPD KOTA BANJARMASIN - Rusmanto Rusmanto; Indra Saputra; Makhriati Makhriati (SEKOLAH TINGGI ILMU EKONOMI NASIONAL (STIENAS) BANJARMASIN, 2019)
Abstract, The research aims to provide empirical evidence of the influence of education levels on the utilization of records of financial statements (CaLK), educational background, experience, social factors in SKPD Banjarmasin City. The independent variables in this study are educational background, experience, social factors, education level. While the dependent variable is financial statement records. The population in this research was 41 SKPD Banjarmasin City. Sampling techniques using purposive sampling samples obtained 82 Heads and Financial management staff at each SKPD Banjarmasin. This is because that someone or something has the information needed for research. The sample taken in this research was the Head and Staff of the SKPD Banjarmasin financial management. The results of the research prove that the level of education, educational background, experience, social factors influence the utilization of financial statement records on the SKPD Banjarmasin.